The Complexity of SARS-CoV-2 Infection and the COVID-19 Pandemic - da Silva Torres, Maria Karoliny; Bichara, Carlos David Araújo; de Almeida, Maria de Nazaré do Socorro; Vallinoto, Mariana Cayres; Queiroz, Maria Alice Freitas; Vallinoto, Izaura Maria Vieira Cayres; dos Santos, Eduardo José Melo; de Carvalho, Carlos Alberto Marques; Vallinoto, Antonio Carlos R. (Frontiers in Microbiology, 2022)
The pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to the death of millions of people worldwide and thousands more infected individuals developed sequelae due to the disease of the new coronavirus of 2019 (COVID-19). The development of several studies has contributed to the knowledge about the evolution of SARS-CoV2 infection and the disease to more severe forms. Despite this information being debated in the scientific literature, many mechanisms still need to be better understood in order to control the spread of the virus and treat clinical cases of COVID-19. In this article, we carried out an extensive literature review in order to bring together, in a single article, the biological, social, genetic, diagnostic, therapeutic, immunization and even socioeconomic aspects that impact the SAR-CoV-2 pandemic. This information gathered in this article will enable a broad and consistent reading of the main aspects related to the current pandemic.